2020
DOI: 10.1097/hjh.0000000000002519
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and pressure wave reflection in the development of isolated diastolic hypertension

Abstract: Objectives: This prospective study was conducted to clarify the significance of augmented pressure wave reflection without accompanying increased arterial stiffness in the development of isolated diastolic hypertension (IDHT). Methods: A total of 3022 Japanese men without hypertension at the start of this study were included in the analyses. The blood pressure, brachial--ankle pulse wave velocity (brachial-ankle PWV), and radial augmentation index (rAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Nonetheless, there is evidence in the current literature that suggests increased stiffness and augmented pressure wave (e.g. abnormal wave reflection) could additively contribute to the onset of hypertension [ 23 , 24 ]. It is possible that the crosstalk between micro-circulation and macro-circulation and the inter-connection between them leads to additive detrimental effects on the circulation due to increased global vascular stiffness [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there is evidence in the current literature that suggests increased stiffness and augmented pressure wave (e.g. abnormal wave reflection) could additively contribute to the onset of hypertension [ 23 , 24 ]. It is possible that the crosstalk between micro-circulation and macro-circulation and the inter-connection between them leads to additive detrimental effects on the circulation due to increased global vascular stiffness [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the value of AIr is slightly higher than the normal health values for people in their mid-20s, 40 which correlates with the slightly higher diastolic blood pressure of the volunteer (130/90 mmHg). 41 In addition, the corresponding fast Fourier transformation (FFT) results shown in Figure 6c indicated that the harmonic components of the collected pulse wave were mainly distributed in the range of 0-10 Hz, corresponding to that of healthy adults, 42 which proved that the response time of the HB sensor meets the requirement of pulse measurement. The calculated heart rate was 78 beats per minute (bpm) according to the first main peak in the FFT spectrum, indicating the health state of the volunteer.…”
Section: Resultsmentioning
confidence: 89%
“…14 The pathogenesis of ISH is enrolled increased arterial stiffness. 30 Furthermore, arterial aging might result in an additional progression in IH-home SBP, which is a risk factor for target-organ damage 31 and diabetic nephropathy. 32 In type 2 diabetes, an association between proteinuria and high BP is strictly related to a higher risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%